Analysis of Vitamin Levels and Deficiencies in Bariatric Surgery Patients. (21st September 2018) - Johnson, Lisa; Ikramuddin, Sayeed; Leslie, Daniel; Slusarek, Bridget; Killeen, Anthony A
Abstract: Background: Both preoperative and postoperative vitamin deficiencies are prevalent in bariatric surgery patients. Previous studies, reviews, and the American Society for Metabolic & Bariatric Surgery (ASMBS) guidelines have noted variability in percent vitamin deficiencies across different populations of bariatric patients, although usually a majority of deficiencies involve vitamin D. We analyzed deficiencies for the four most commonly measured vitamins—B1, B12, A, and D—in sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB) patients in order to assess nutritional deficiencies. Methods: A retrospective chart review of 358 SG and 110 RYGB patients who had recorded vitamin levels and a bariatric procedure from April 2012 to April 2016 was performed. Data were collected for vitamins A, B1, B12, and D. Statistical analyses were performed using Stata. The percentages of patients with vitamin deficiencies were analyzed by group: preoperative, ≤1 year postoperative, and >1 year postoperative period. Using multilevel mixed-effects linear regression analyses, we determined if the change in vitamin level was significant over time (months) and by surgery type. This study was approved by the University of Minnesota IRB. Results: There were no significant differences between SG and RYGB patients in baseline (preop) levels for any vitamin. Deficiencies of B1 and A increased during the first-year postsurgery (between 2% and 11%) in both RYGB and SG patients but improved in subsequent years. Over multiple years, vitamin B1 levels increased following surgery ( P < .001), but vitamin A levels did not change significantly. RYGB patients had significantly lower vitamin A levels than SG patients. Vitamin B12 deficiencies were the least common during the preoperative and postoperative period at ≤2%, and levels increased postoperatively by an average of 14 pg/mL/month with no significant difference between surgery types. Vitamin D deficiencies decreased during the first year after surgery, from ~27% preoperative deficiencies to 5.2% in SG and 11.5% in RYGB patients. In the ≥1-year postoperative period, 13.4% of SG patients and 20.3% of RYGB patients had deficiency of vitamin D, with RYGB patients having significantly lower vitamin D levels than SG patients by 3.6 ng/mL. Conclusions: Vitamin A and B1 deficiencies increased within the first year but improved after the first year postsurgery. Vitamin B12 deficiencies were rare, and levels of vitamin B12 significantly increased after surgery. Vitamin D deficiencies became less common within the first year of surgery. Interestingly, the multilevel model demonstrated a significant difference between RYGB and SG for the two fat-soluble vitamins. Collection of data for additional years is needed to understand the long-term status of vitamin deficiencies in bariatric surgery patients.